Henry's F. Pittier's Contributions to the Geography of Costa Rica and Venezuela. - Yacher, Leon I. (1995)
Keywords: dept.egm; faculty_collection; sabbatical_report

A Wholistic View of Environmental Education. Rationale. - Stone, A. Harris (Spring ; Center of the environment., 1991)
Keywords: dept.egm; faculty_collection; sabbatical_report

Basic Botany - Avery, David F.; Smith, Dwight G. (Simon and Schuster Custom Publishing, 1994)
Keywords: Botany; dept.egm; faculty_collection

Connecticut Birding Guide - Devine, Arnold; Smith, Dwight G. (Thompson-Shore, 1996)
Keywords: Birding sites; Connecticut; Guidebooks; Guidebooks; Bird watching; dept.egm; faculty_collection

Political Geography - Glassner, Martin Ira (J. Wiley, 1996)
Keywords: Political geography; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff, 1995)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; dept.egm; faculty_collection

Zoology Laboratory Guide - Avery, David F.; Nelson, Vernon A.; Pellegrino, Peter Edward; Smith, Dwight G.; Turko, Alexander A.; Burian, Steven K.; Green, Laura A.; Duman, Mathew (Southern Connecticut State University, 1994)
Keywords: Laboratory manuals; Zoology; dept.egm; faculty_collection

All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J.; James, Preston E.; James, Eileen W. (Wiley & Sons, 1993)
Keywords: Geography; History; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Sold and distributed in the U.S.A. and Canada by Kluwer Academic Publishers, 1991)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

Neptune's Domain: A Political Geography of the Sea. - Glassner, Martin Ira (1990)
Keywords: Maritime law; Political geography; dept.egm; faculty_collection

Navigational restrictions within the new LOS contexts: Georgaphical Implications for the United States. Lewis M. Alexander, Peace Dale, RI: Offshore Consultants, Inc., December 1986 - Glassner, M.I. (Political Geography Quarterly, 1991)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Foxwoods Casino Resort: An unusual experiment in economic development - D'Hauteserre, A.-M. (Economic Geography, 1998)
The Foxwoods Casino Resort owned by the Mashantucket Pequots of Connecticut is the largest gambling casino in the Western world. The Pequots' Connecticut location enabled the tribe to open a casino, with accessibility to a large market and limited competition. The opening of Foxwoods is also the result of changes in relationships between Americans and Indians and shifts in American attitudes toward gambling. As attitudes and laws change, however, there is little chance that another Indian Foxwoods will be created here or elsewhere in the United States.
6 citations (Crossref) [2023-10-31]
Keywords: American Indian sovereignty; Connecticut; Gambling; Mashantucket Pequots; Pequots people; USA; Connecticut; casino; dept.egm; gambling; indigenous population; recreational activity

The emergence and development of geographic thought in new england - Martin, Geoffrey J (Economic Geography, 1998)
Some of the early settlers of New England brought with them the works and thought of European geographers, notably Ptolemy, Munster, Cluver, Carpenter, and Varenius. Beginning in the 1600s the work of British geographers Gordon and Salmon and Guthrie and Pinkerton was acknowledged, preceding that of Jedidiah Morse, “Father of American Geography.” Morse led the way for a large number of geography texts written by Americans, emphasizing North America and characterized by Varenius's special geography. Early collegiate developments in New England geography were led by Harvard and Yale universities, the College of Rhode Island (later renamed Brown University), and Dartmouth College. The 20 or so normal schools throughout New England, introduced in the middle 1800s, constituted a nursery for geographic education. Also noted are more recent college and university geography departments established throughout the region, including notably Clark University. The founding of societies and associations in New England also furthered the cause of geography.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-602-143-244-317 tex.type: [object Object]
Keywords: Geography; Harvard; History; Morse; USA; New England; Varenius; Yale; dept.egm; geographical thought; geography education; history of geography

Disneyland paris: A permanent economic growth pole in the francilian landscape - d'Hauteserre, Anne-Marie (Progress in Tourism and Hospitality Research, 1997)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-877-700-234-160 tex.type: [object Object]
Keywords: dept.egm

Resolving the problems of land‐lockedness - Glassner, Martin Ira (Geopolitics, 1997)
The professional literature on land-locked states has increased substantially in the past two decades. There is now a considerable body of writings by people in many countries around the world reporting on, inquiring into or carefully analysing most aspects of land-lockedness from various disciplinai and national viewpoints. In addition, there is a roughly equally large body of material related to land-lockedness produced by the United Nations and its organs and affiliates; by other intergovernmental organisations, including many regional and subregional groups; and by private consultants and consulting firms, chiefly in the fields of economics and engineering. © 1998 Frank Cass.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-296-698-491-722 tex.type: [object Object]
Keywords: dept.egm

A response to dimitri ioannides, “Strengthening the ties between tourism and economic geography: A theoretical agenda.” - d'Hauteserre, Anne-Marie (The Professional Geographer, 1996)
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00154 tex.type: [object Object]
Keywords: dept.egm

The rich neighbor policy: rockefeller and kaiser in brazil - Cobbs,EA - Yacher, L (Journal of Developing Areas, 1996)
tex.unique-id: ISI:A1996UF91000015
Keywords: dept.egm; ⛔ No DOI found

Geography and national identity - hooson,d - Glassner, M (International Affairs, 1995)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1995RL04900030
Keywords: dept.egm

Book review: France's overseas frontier: Départements et territoires d'outre-mer: Robet Aldrich and John Connell, Cambridge University Press, 1992 - Glassner, Martin Ira (Political Geography, 1995)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book Review: Nauru: Environmental damage under international trusteeship: Christopher Weeramantry, Oxford University Press, Melbourne, 1992 - Glassner, Martin Ira (Political Geography, 1995)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book Review: The Dutch Caribbean: Prospects for democracy: Betty Sedoc-Dahlberg, Gordon and Breach, New York, 1990 - Glassner, Martin Ira (Political Geography, 1995)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Hartshorne,richard, 1899-1992 - in-memoriam - Martin, GJ (Annals of the Association of American Geographers, 1994)
8 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1994PH93800007
Keywords: dept.egm

Geography and the human spirit - buttimer,a - Martin, GJ (Professional Geographer, 1994)
tex.unique-id: ISI:A1994NQ42000015
Keywords: dept.egm; ⛔ No DOI found

Pioneers of modern geography - translations pertaining to german geographers of the late 19th and early 20th centuries - west,rc - Martin, GJ (Professional Geographer, 1994)
tex.unique-id: ISI:A1994MW89600038
Keywords: dept.egm; ⛔ No DOI found

Tagging and migration of the American lobster Homarus americanus - Haakonsen, H. O.; Anoruo, A. O. (Reviews in Fisheries Science, 1994)
Three types of tags, external, internal, and sonic, have been used to study migration of the American lobster Homarus americanus. Tag loss and interpretation of returned tag data are serious problems associated with internal and external tags. Lobster tracking using sonic tags is still in the pilot stage. Lobster migration is redefined to include horizontal and vertical displacements. Depth of displacement is a more reasonable measurement of lobster migration than horizontal distance traveled. Two distinct lobster populations are discernable based on their ecological habitation and migratory behavior. Evidence in this review suggests that the deep-sea lobster migrates, whereas the coastal lobster may move within a limited range. © 1994, Taylor & Francis Group, LLC. All rights reserved.
20 citations (Crossref) [2023-10-31] Citation Key Alias: pop00045 tex.type: [object Object]
Keywords: Homarus americanus; coastal lobster; deep-sea lobster; dept.egm; migration

Recent contributions of the United Nations to political geography - Glassner, Martin Ira (Political Geography, 1994)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-931-043-628-079 tex.type: [object Object]
Keywords: dept.egm

The tide flows on - Glassner, Martin Ira (Ocean Yearbook Online, 1994)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/045-497-077-820-496
Keywords: dept.egm

Book Review: Smith, H.D. and Vallega, A., editors, 1991: The development of integrated sea-use management. London: Routledge. xvi + 284 pp. £45.00 cloth. ISBN: 0 415 03816 2 - Glassner, Martin Ira (Progress in Human Geography, 1993)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1993LH35100033 tex.unique-id: [object Object]
Keywords: book.review; dept.egm

Book Review: Review essay: Recent books on marine affairs - Glassner, Martin Ira (Ocean Development and International Law, 1993)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-628-990-489-766 tex.type: [object Object]
Keywords: book.review; dept.egm

Management of marine resources as a binding force in the Eastern Caribbean - Glassner, Martin Ira (Ocean & Coastal Management, 1993)
The history of the Commonwealth Caribbean is replete with failed attempts at various degrees of economic and political integration. The Caribbean Sea itself is rather poor in both living and non-living resources, and the entire region-land and water-is suffering from varying degrees of environmental degradation. This article suggests that regional co-operation in the management of marine resources, particularly in the Anglophone islands of the Eastern Caribbean, could serve as an 'engine of integration'-something previous attempts lacked. There is no assurance that such an effort would be successful, however, despite good intentions, co-operation in many areas at present and some real cultural affinities. The centrifugal forces at work here are still very powerful, including parochialism and the scarcity of resources other than sun, sand and sea. © 1993.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/060-406-509-332-347 tex.type: [object Object]
Keywords: Anglophone islands; Caribbean; Caribbean; (East); Centrifugal forces; Coastal engineering; Commonwealth Caribbean; Eastern caribbean; Engine of integration; Environmental degradation; Environmental impact; Laws and legislation; Management; Management of marine resources; Scarcity of resources; dept.egm; developing country; economic and political integration; economic association; environmental degradation; environmental resource management; marine resource management; marine resources; regional cooperation; resources management

The political geography of the sea - Glassner, Martin Ira (Canadian Geographer, 1993)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-048-621-388-635 tex.type: [object Object]
Keywords: dept.egm

Enhancing teaching excellence through a scientist-science teacher collaborative process. - Haakonsen, Harry O; Stone, A Harris; Tomala, Gail; Hageman, Susan (Journal of Science Teacher Education, 1993)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-630-213-283-541 tex.type: [object Object]
Keywords: dept.egm

The times atlas and encyclopedia of the sea - couper,a - Glassner, MI (Marine Policy, 1992)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1992HH67000013
Keywords: dept.egm

History of geography archives — A world directory - Martin, G J (GeoJournal, 1992)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-242-427-891-485 tex.type: [object Object]
Keywords: dept.egm

The geography of geographers - Martin, G J (GeoJournal, 1992)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-501-533-569-19X tex.type: [object Object]
Keywords: dept.egm

Review: international law and organization: the fisheries regime of the exclusive economic zone, EEC fisheries LawTHE FISHERIES REGIME OF THE EXCLUSIVE ECONOMIC ZONEDordrechtMohamed dahmani, boston, lancaster: martinus nijhoff, 1987, xii, 188 pp, US71.50EEC FISHERIES LAWChurchillRobin R.Dordrecht, boston, lancaster: martinus nijhoff, 1987, xxviii, 299 pp, US80.00 - Glassner, Martin Ira (International Journal, 1991)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Annual-Review of Ocean Affairs - Law and Policy, Main Documents 1988, Vol 3 - Un-Off-Ocean-Affairs-Law-Sea - Glassner, MI (Marine Policy, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991GQ16500007
Keywords: dept.egm

Book Review: The exclusive economic zone - regime and legal nature under international-law - vicuna,fo - Glassner, Martin Ira (Marine Policy, 1991)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

The Age of the Arctic: Hot Conflicts and Cold Realities. By Gail Osherenko and Oran R. Young. Cambridge: Cambridge University Press, 1989. 316p. $59.50. - Glassner, Martin Ira (American Political Science Review, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991FE99500108, lens.org/119-981-059-692-619 tex.unique-id: [object Object]
Keywords: dept.egm

Development and Social-Change in the Pacific Islands - Couper,ad - Glassner, MI (Political Geography Quarterly, 1991)
0 citations (Crossref) [2023-10-31] tex.orcid-numbers: PATTANAYAK, MANORANJAN/0000-0002-5661-6563 tex.researcherid-numbers: PATTANAYAK, MANORANJAN/N-7858-2017 tex.unique-id: ISI:A1991EQ30700011
Keywords: dept.egm

International Space Policy - Legal, Economic and Strategic Options for the 20th-Century and Beyond - Papp,ds, Mcintyre,jr - Glassner, MI (Political Geography Quarterly, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991EQ30700010
Keywords: dept.egm

The law of the sea and international shipping: AngloSoviet post-UNCLOS. W.E. Butler (ed). New York, London and Rome: Oceana Publication, 1985 - Glassner, M.I. (Political Geography Quarterly, 1991)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book Review: Die seerechtliche verteilung von nutzungsrechten; rechte der binnenstaaten in der ausshliesslichen wirtschaftszone: Gerhard Hafner, Vienna and New York: Springer Verlag, 1987 - Glassner, Martin Ira (Political Geography Quarterly, 1991)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-830-542-556-808 tex.type: [object Object]
Keywords: book.review; dept.egm

The frontiers of earth — and of political geography: The sea, Antarctica and outer space - Glassner, Martin Ira (Political Geography Quarterly, 1991)
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/181-511-227-722-816 tex.type: [object Object]
Keywords: dept.egm; ⛔ No DOI found

The Fisheries Regime of the Exclusive Economic Zone - Dahmani,m - Glassner, MI (International Journal, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991HC51100012
Keywords: dept.egm

North-South Perspectives on Marine Policy - Morris,ma - Glassner, MI (Journal of Developing Areas, 1990)
tex.unique-id: ISI:A1990CV37800023
Keywords: dept.egm; ⛔ No DOI found

The legal regime of enclosed or semi-enclosed seas - the particular case of the mediterranean - vukas,b - Glassner, MI (Marine Policy, 1990)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1990CE16700015
Keywords: dept.egm

The theory and history of ocean boundary-making - johnston,dm - Glassner, MI (Political Geography Quarterly, 1990)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1990CJ06800010
Keywords: dept.egm